Community Security and Justice under United Nations Governance: Lessons from Chiefs' Courts in South Sudan's Protection of Civilians Sites. Issue 1 (7th December 2017) - Ibreck, Rachel; Pendle, Naomi
This article examines the public authority of chiefs' courts within the United Nations Mission in South Sudan (UNMISS) Protection of Civilians Sites (PoCs). After December 2013, UNMISS peacekeepers opened the gates of their bases to around 200, 000 civilians fleeing war. This unintentionally created a legal and political anomaly. Over time, conflicts and crimes rose within the sites, and UNMISS improvised a form of administration. But while the internationals sought technical solutions, people displaced within the sites turned to familiar 'customary' methods to manage problems of insecurity, establishing chiefs' courts. The PoC sites became an arena of plural authorities, with chiefs working alongside camp administrators, peacekeepers and humanitarian actors. We explore how and why the chiefs responded to insecurity within the sites and whether they engaged with, or diverged from United Nations actors and international norms. We demonstrate that justice remains central to the provision of security in contexts of war and displacement. International peace interventions are rightly wary of 'customary' justice processes that prioritise communities and families at the expense of individual rights, but this unique case shows that they are sources of trust and consistency that are resilient, adaptable and can contribute to human security.